Evidence of platelet sensitization to ADP following discontinuation of clopidogrel therapy in patients with stable coronary artery disease. (September 2015) - Lordkipanidzé, Marie; Diodati, Jean G.; Schampaert, Erick; Palisaitis, Donald A.; Pharand, Chantal
Abstract Epidemiological studies have linked clopidogrel discontinuation with an increased incidence of ischemic events. This has led to the hypothesis that clopidogrel discontinuation may result in a pharmacological rebound. We evaluated the impact of clopidogrel discontinuation on platelet function. Platelet aggregation was measured by light transmission aggregometry (LTA) in response to adenosine diphosphate (ADP) 0.5, 1, 1.5, 2.5, 5 and 10 µM and by VerifyNow® P2Y12, in 37 clinically stable coronary artery disease (CAD) patients scheduled to discontinue clopidogrel treatment, and 37 clinically stable CAD patients not taking clopidogrel. Platelet function was assessed the day before clopidogrel cessation and 1, 3, 7, 14, 21 and 28 days after. Clopidogrel had been initiated a median of 555 days (ranging from 200 to 2280 days) before the treating cardiologist recommended its discontinuation. All participants were taking aspirin, most commonly 80 mg daily although a minority was prescribed 325 mg daily. Following clopidogrel discontinuation, VerifyNow® P2Y12 did not detect any rebound platelet activity, but ADP-induced LTA showed platelet sensitization to ADP, particularly at low ADP levels. Increased platelet activity was detectable seven days after clopidogrel cessation and remained higher than in controls 28 days after discontinuation. No clinical event occurred in any of the participants during the 28 days following clopidogrel cessation. In conclusion, platelet sensitization to ADP as a consequence of chronic clopidogrel administration may partially explain the recrudescence of ischemic events following clopidogrel discontinuation in otherwise stable coronary artery patients.